The research of ammonium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazole-3-yl)thio)acetate (PKR-177) influence on biochemical indices in rats blood under hepatitis initiated by tetrachloride methane - Shcherbyna R. О.; Samura Т. О.; Kyrychko, B. P.; Zvenihorodska Т. V.; Hyrenko, I. V. (Zaporozhye Medical Journal, 2017)
Hepatitis is a disease which causes liver inflammation. The most widespread hepatitis pathogens are hepatitis viruses but it can also be caused by other infections such as some toxic substances and auto-immune diseases. The aim of research. The research of the influence of ammonium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazole-yl-3)thio)acetate (PKR-177) on biochemical indices of rats blood under hepatitis caused by tetrachloride methane. The materials and methods of research. 1 % aqueous solution of PKR-177 substance was used as the material of this research. The studying was held according to methodological recommendations of “Preclinical research of medical substances”. Experimental animals were clinically observed. Evaluation of biochemical and functional indices of their organisms (incl. liver) was carried out 24 hours after the last injection of tetrachloride methane. Results and their discussion. Clinical analysis demonstrated that hypodermic injection of oil solution of tetrachloride methane resulted in abrupt deterioration of the overall health condition of experimental animals. They were not keen to move, gathered together in groups, partially refused to eat. Entire refusal from food was observed after repeated injection of tetrachloride methane. Animals injected with PKR-177 and Thioprotectin intensively consumed water, ate food in small portions. After 24 hours blood tests of all animals under research were made for profound biochemical studying. As a result of the reproduction of acute toxic lesions (in comparison with intact animals) a violation of the functional capacity of the liver was noted. In the serum this was manifested by a sharp decline in activity of transaminases (ALT and AST). This occurred on a background of increased activity of lactate dehydrogenase and gamma glutamyl transpeptidase. The injection of carbon tetrachloride produced tendency to decrease the content of albumin, total protein, albumin/globulin ratio, glucose level, cholesterol, triacylglycerides, total bilirubin and a-amylase activity. Conclusions. The influence of ammonium 2-((4-amino-5-(morfolinomethyl)-4H-1,2,4-triazole-3-yl)thio)acetate (PKR-177) on blood biochemical parameters in rats with hepatitis caused by tetrachlormethan was studied. 27 Biochemical and functional parameters of the blood of experimental animals were investigated. In the result of experiment it was found that the activity of ALT, AST enzymes was higher in animals injected by the PKR-177 solution compared to rats from the first and fourth experimental groups.